US-Pakistan row : implications for Afghanistan end goals - Bibhu Prasad Routray (2012)
The ongoing war of words between the United States and Pakistan is a clash of diverse end goals of these countries in Afghanistan. It also represents a contest between a declining superpower and a country that believes it simply cannot lose.